Antibiotic Therapy for Culture-Proven Bacterial Overgrowth in Children With Intestinal Failure Results in Improved Symptoms and Growth. Issue 3 (1st June 2022) - Culbreath, Katherine; Knell, Jamie; Keefe, Gregory; Han, Sam M.; Hong, Charles R.; Riley, Heather B.; Liu, Enju; McAdam, Alexander J.; Modi, Biren P.; Jaksic, Tom; Duggan, Christopher P.; Carey, Alexandra N.
Abstract : Objectives: To evaluate symptoms, enteral tolerance, growth, and antibiotic regimens in pediatric intestinal failure (IF) patients after treated with antibiotic therapy for small bowel bacterial overgrowth (SBBO). Methods: Single-center retrospective review of children 0–18 years with IF with endoscopic cultures demonstrating >10 5 CFU/mL from 2010 to 2017. Symptoms, enteral tolerance, growth, and antibiotic regimens were evaluated at the time of endoscopy and 6 months later. Results: Of 505 patients followed in our intestinal rehabilitation program, 104 underwent upper gastrointestinal endoscopy and 78 had positive duodenal cultures. Clinical data pre- and post-endoscopy were available for 56 patients. Compared to baseline, in the 6 months following targeted antibiotic treatment, children showed significant improvement in emesis or feeding intolerance (58.9% vs 23.2%, P < 0.001), abdominal pain (16.1% vs 7.1%, P = 0.02), high stool output (42.9% vs 19.6%, P = 0.002), and gross GI bleeding (19.6% vs 3.6%, P = 0.003). Mean BMI-for-age z scores increased significantly (−0.03 ± 0.94 vs 0.27 ± 0.82, P = 0.03); however, height-for-age z scores, weight-for-age z scores, and percent of calories from enteral intake were not significantly different after therapy. Antibiotic regimens remained highly variable. Conclusions: Children with IF and culture-positive SBBO showed significant improvement in symptoms and BMI-for-age z scores after duodenal culture with subsequent targeted antibiotic therapy. Longer follow-up may be needed to detect improvements in linear growth and percent of calories from enteral feeds. Antibiotic regimens remain highly variable. Long-term consequences of chronic antimicrobial therapy, including antimicrobial resistance, remain unknown. Prospective studies focused on standardizing duodenal sampling technique, correlating culture and pathology data, and evaluating antibiotic resistance patterns are needed.